Biomechanical effects of the novel series LVAD on the aortic valve. (December 2020) - Gao, Bin; Kang, Yizhou; Zhang, Qi; Chang, Yu
Highlights: BJUT-II VAD is a novel kind of left ventricular assist device. This is the first study on its biomechanical effect on the aortic valve. In this study, the geometric model of BJUT-II VAD is virtually implanted into the ascending aorta, and the impeller of BJUT-II VAD rotates to produce the real blood flow environment for the aortic valve. the results demonstrated that the series type LVAD could provide a good biomechanical environment for the aortic leaflets, thus reducing the risk of aortic valve disease. Abstract: Background and Objective: The series type of LVAD (i.e., BJUT-II VAD) is a novel left ventricular assist device, whose effects on the aortic valve remain unclear. Methods: The biomechanical effects of BJUT-II VAD on the aortic valve were investigated by using a fluid–structure interaction method. The geometric model of BJUT-II VAD was virtually implanted into the ascending aorta to generate the realistic flow pattern for the aortic valve (i.e., support). In addition, the biomechanical states of the aortic valve without BJUT-II VAD support was computed as control (i.e., control case). Results: Results demonstrated that the biomechanical effects of BJUT-II VAD were quite different from that resulting from traditional "bypass LVAD." Compared with those in the control case, BJUT-II VAD support could significantly reduce the stress load of the leaflet (maximum stress, 0.5 MPa in the control case vs. 0.12 MPa in the support case). Similarly, the rapid valve opening time (100 ms in the control case vs. 175 ms in the support case) and rapid valve closing time (50 ms in the control case vs. 150 ms in the support case) in the support case were obviously longer than those in the control case. Moreover, BJUT-II VAD support reduced retrograde blood flow during the diastolic phase and significantly changed the distribution of WSS of the leaflets. Conclusions: In summary, while unloading the left ventricle, BJUT-II VAD could provide beneficial biomechanical states for the aortic leaflets, thereby reducing the risk of aortic valve disease.